Si Carancal laban sa hangin Carancal fights the wind - Villanueva, Rene O.; Albano, Kora Dandan; Pastor, Boots S. Agbayani (Quezon City Lampara Publishing House, Inc., 2008)
In this story, wherein Carancal fights the wind in order to recover the lady binukot, the author gives emphasis to the concern and love for others. It also highlights the importance of faith and confidence in one's self as well as courage despite personal and/or physical limitations.
Text in English and Filipino.
Keywords: Folklore -- Philippines